Asymptotic Behavior for Global Smooth Solution to a One-dimensional Nonlinear Thermoviscoelastic System (Journal of Partial Differential Equations, 1999)
This paper is concerned with asymptotic behavior, as time tends to infinity, of globally defined smooth (large) solutions to the system in one-dimensional nonlinear thermoviscoelasticity. Our results show that the global smooth solution approaches to the solution in the H¹ norm to the corresponding stationary problem, as time tends to infinity.
Keywords: Global solution; asymptotic behavior; a priori estimates